Peptic ulcers after the Great East Japan earthquake and tsunami : possible existence of psychosocial stress ulcers in humans - Kanno, Takeshi; Iijima, Kastunori; Abe, Yasuhiko; Koike, Tomoyuki; Shimada, Norihiro; Hoshi, Tatsuya; Sano, Nozomu; Ohyauchi, Motoki; Ito, Hirotaka; Atsumi, Tomoaki; Konishi, Hidetomo; Asonuma, Sho; et al. (Journal of gastroenterology, 2013)
Background Societal stress derived from an event that affects the whole society, e. g., a natural disaster, provides a unique, indirect way of determining the relationship between psychological stress and peptic ulcer disease in humans. In this study, we investigated the changing patterns of the incidence of peptic ulcers before and after the Great East Japan earthquake, which occurred on 11 March, 2011. Methods Clinical data of patients with peptic ulcers were retrospectively collected during the 3 months after the earthquake (2011) from 7 major hospitals in the middle of the stricken area, and were compared with the data for the same period of the previous year (2010). The eligible subjects were classified into four groups according to Helicobacter pylori infection status and intake of nonsteroidal anti-inflammatory drugs (NSAIDs). Results The incidence of all types of peptic ulcers was 1.5-fold increased after the earthquake, and in particular, the incidence of hemorrhagic ulcers was 2.2-fold increased; the gastric ulcer/duodenal ulcer ratio in hemorrhagic ulcers was also significantly increased ( p < 0.05). Regarding the etiology of the peptic ulcers, the proportion of non- H. pylori and non-NSAID ulcers was significantly increased, from 13 % in 2010 to 24 % in 2011 after the earthquake ( p < 0.05). Conclusion In addition to the increased incidence of peptic ulcers, compositional changes in the disease were observed after the Great East Japan earthquake. The significant increase in the proportion of non- H. pylori and non-NSAID ulcers after the earthquake indicated that psychological stress alone induced peptic ulcers in humans independently of H. pylori infection and NSAID intake.